Mortalidade neonatal : fatores de risco no município de Maringá-PR em 2003 e 2004 - Maran, Edilaine (2006)
The neonatal mortality is the main component of the infant mortality in proportional terms, and its reduction is a great challenge for the health services. Therefore, studies about the risk factors are important in the elucidation of decisive elements, because they subsidize the interventions towards the reduction of the possible deaths in this period. The purpose of this study was identifying the risk factors for the neonatal mortality, in the live newborn population, children of mothers resident in the Municipal district of Maringá - PR in the years 2003 and 2004. It was a transversal study, with secondary data obtained from the Live Newborn System of Information and System of Information of Mortality. The study population was of 8,285 live newborn, being 56 neonatal deaths. Univariate and multivariate analyses of the neonatal obstetric and maternal variables were accomplished. The deaths prevailed in early neonatal period (78.6%), in male individuals (62.5%), in newborns(NB) of low birth weight (78.6%), in premature ones (78.6%), in NB that presented Apgar <7 at the first minute (78.2%) and Apgar >7 at the fifth minute (56.4%), in NB whose mothers presented only one gestation (87.5%), NB of primiparous mothers (57.1%), in NB whose mothers that had >7 prenatal visits (53.6%), in NB whose mothers were from 20 to 34 years old (60.7%) and in NB mothers who had 8-11 years of education (55.3%). The basic causes of the most frequent death were the affections originated in the perinatal period (82.1%) following by the congenital malformations (16.1%). Associations statistically significant to the neonatal mortality such as birth weight, gestation length, Apgar at the first and fifth minutes of life, malformation/abnormality, childbirth type, number of prenatal care visits and mother's age were presented. In the multivariated analysis, the variables that confirmed to be of risk factors were gestation length, birth weight, Apgar at the first and fifth minutes of life, and malformation/abnormality. These results indicate that the health professionals need review the meaning and reflect upon the practices of attendance provided to the pregnant women, parturients, and newborns during pregnancy, labor and conception.